Analysis of Factors Influencing Carbon Emissions Disclosure - Mavira Fitri Muliani; Siti Nur Hadiyati (International Journal of Business, Economics, and Social Development, 2026)
The main objective of this study is to examine the elements that influence carbon emission disclosure using a quantitative approach. This study covers companies in the chemical and raw materials sector listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. The sample was taken using a specific sampling technique, resulting in 33 companies consisting of a total of 99 observation units. Data analysis was performed by applying multiple linear regression with independent variables such as industry sector, company size, leverage, environmental performance (PROPER ratings), board independence and audit committee. Carbon emissions disclosure was measured based on the GRI 305 standard using content analysis with a dummy approach. The findings demonstrated that while leverage had no discernible impact on carbon emission disclosure, type of industry,size, environmental performance, board independence, and audit committee did.